Evaluating the Effectiveness of Radio Drama in Promoting Women’s Empowerment in Niger State - Ogali, Eze Eze (African Journal of Stability and Development (AJSD), 2025)
This study evaluated the effectiveness of radio drama as a strategic communication tool for promoting women’s empowerment in Niger State, Nigeria. Using a mixed-methods descriptive research design, data were collected from 300 women across Niger, Abuja Municipal Area Council (AMAC), and Nasarawa State. Quantitative data were complemented by focus group discussions and key informant interviews. The study was anchored in the Entertainment-Education strategy and Social Learning Theory, which underscore the capacity of storytelling to inform and transform societal norms. Findings revealed that over 78% of respondents listened to radio drama at least occasionally, with a significant majority describing the content as relevant to their lived experiences. Participants reported increased self-confidence, engagement in family decision-making, and a heightened awareness of women's rights and agency. However, the study also identified limitations, including limited feedback mechanisms, cultural resistance in some rural areas, and the absence of clear pathways for translating awareness into concrete action. The study concluded that while radio drama is a potent tool for raising consciousness and challenging patriarchal norms, its impact is mediated by socio-cultural and infrastructural factors. It recommended that programme developers localise content linguistically and culturally, incorporate listener feedback, and strengthen partnerships with community leaders and support organisations. Ultimately, the strategic use of radio drama can contribute significantly to gender equality when embedded in a holistic, participatory development communication framework.